Penerapan Model Pembelajaran Inside Outside Circle pada Pembelajaran IPAS Siswa Kelas IV Sekolah Dasar - Aprilia, Dian; Supriyanto, Supriyanto; Hamdan, Hamdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to measure the achievement of science learning outcomes of fourth grade students of SD Negeri Trans Ciptodadi after the application of the Inside Outside Circle learning model. The method used is a quantitative method with an experimental approach with the design used is a pre-experimental one-group pretest-posttest type. The results of the study showed that the average score of students at the time of the Pre-Test (Initial Test) was 48.44, then after participating in science learning using the Inside Outside Circle learning model, they got an average score of the Post-Test (Final Test) of 87.19 with a percentage of 95%. While in the calculation of the Z test, Zcount 6.83 ≥ Ztable 1.64 was obtained, so Ha was accepted Ho was rejected. The conclusion of this study is that the application of the Inside Outside Circle learning model can significantly describe the Learning Objective Achievement Criteria (KKTP). Keywords: Learning Outcomes, IPAS, Learning Models.